2014
DOI: 10.1016/j.adengl.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic Findings for the Early Detection of Melanoma: An Analysis of 200 Cases

Abstract: Dermoscopy facilitates the diagnosis of melanoma and could be useful for differentiating between melanoma in situ and invasive melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 23 publications
5
19
1
4
Order By: Relevance
“…All three dermoscopic variables showed a P-value less than 0.05. Our data confirmed that these were dermoscopic patterns indicative of melanomas [21][22][23][24]. Moreover, we found the presence of blue-white veil in 33.09% of melanomas.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All three dermoscopic variables showed a P-value less than 0.05. Our data confirmed that these were dermoscopic patterns indicative of melanomas [21][22][23][24]. Moreover, we found the presence of blue-white veil in 33.09% of melanomas.…”
Section: Discussionsupporting
confidence: 93%
“…Discordance on the presence/absence of these patterns was only 8.4% (27 dysplastic nevi and nine in-situ melanomas) ( Table 3). The choice of these three parameters was made on the basis of the consideration that blue-white veil, regression and vascular structure polymorphism are dermoscopic parameters that strongly correlate with melanoma [21][22][23][24]. Moreover, in our previous studies such dermoscopic patterns were not well covered by the computer-assisted evaluation.…”
Section: Medical History and Dermoscopic Datamentioning
confidence: 99%
“…Noktalar ise globüllerden daha küçük dermoskopik yapılardır ve dermisteki pigmente makrofajları veya epidermisteki tekli ya da küçük agregatlar şeklinde bulunan melanom hücrelerini temsil etmektedir 1 . Melanomların yaklaşık %44'ünde gözlendiği belirtilen düzensiz nokta/globüllerin melanom tanısı için sensitivitesi %75, spesifitesi ise %64 olarak bildirilmekte olup radyal faz ile mikro-invaziv evreyi gösterdiği düşünülmektedir 1,22 . Bizim olgularımızda da benzer şekilde ince, in situ, mitoz oranı <1, LVİ (-), ülserasyon (-) ve regresyon (-) olan melanomlarda düzensiz nokta/globüllerin daha yüksek oranda gözlendiği belirlenmiş, ancak istatistiksel olarak anlamlılık izlenmemiştir.…”
Section: Discussionunclassified
“…Mavi-beyazımsı tül, Ciudad-Blanco ve ark. 22 tarafından daha çok invaziv melanomlarda olmak üzere ortalama %22 oranda gözlenmiştir. Benzer şekilde Silva ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation